THE ROLE OF DITRESKRIMUM OF THE CENTRAL JAVA REGIONAL POLICE IN TACKLING HOARDING OF MASKS DURING THE COVID-19 PANDEMIC - rizeth rizeth (Universitas 17 Agustus 1945 Semarang, 2021)
The public’s obligation to wear masks during the Covid-19 pandemic has caused the demand for masks in the market to increase. Some people use this to seek economic benefits by hoarding masks and reselling them at high prices, causing people to experience difficulties and panic in getting masks to protect themselves from exposure to the coronavirus. In this study, problems were formulated about how the roles and obstacles faced by Ditreskrimum at the Central Java Regional police were developed in overcoming the hoarding of masks during the Covid-19 pandemic. The approach method used is empirical juridical. The research specification is descriptive-analytical. The data used are secondary data and primary data as a complement, obtained from literature studies and interviews, then analyzed qualitatively. The theoretical foundations used are role theory, countermeasures theory, discretionary concept, hoarding theory, public welfare theory, and the Ditreskrimum role. The study results are that the Ditreskrimum acts as a law enforcement institution above the community and can create a conducive security and social order situation during the Covid-19 pandemic. There is no legal basis for investigators to ensnare hoarders who claim that masks are necessities or essential items that should not be stockpiled during the Covid-19 pandemic as a recommendation is that the government make new regulations in the form of laws, Presidential Regulations, and related Ministerial Regulations which contain the determination of the status of specific goods that are considered essential and needed by many people during an emergency to become necessities or essential goods to strengthen the law that previously existed so that the perpetrators of hoarding can be charged with criminal provisions.